WEAKLY COMMUTATIVE \(n\)-SEMIGROUPS - Kržovski, Pano (Matematichki Bilten, 1992)
In this note we generalize the notion of weakly commutative semigroup to the \(n\)-ary case and we show that every weakly commutative \(n\)-semigroup is an \(n\)-semilattice of archimedean \(n\)-semigroups.